2015
DOI: 10.12816/0011209
|View full text |Cite
|
Sign up to set email alerts
|

Effective Talent Management : Key to Organisational Success

Abstract: Today's global economy has created a more complex and dynamic business environment in which most organizations must learn to compete effectively to achieve success and sustainable growth. Workforces around the world have become larger, increasingly diverse, more educated, and more mobile. There is considerable evidence that organizations worldwide face formidable talent challenges. The ability to attract, develop, and retain a needed supply of critical talent is a challenge facing all organizations. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…The present study has reported that talent management has a significant effect on employee engagement and organizational effectiveness. This is consistent with the research work of Ifeoma et al (2015); Guest (2014); Abbasi et al (2010). Recently, Lyria et al (2017) studied the relationship between talent management and organizational performance in Kenya and found that talent management creates a competitive edge which directly improves the company performance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study has reported that talent management has a significant effect on employee engagement and organizational effectiveness. This is consistent with the research work of Ifeoma et al (2015); Guest (2014); Abbasi et al (2010). Recently, Lyria et al (2017) studied the relationship between talent management and organizational performance in Kenya and found that talent management creates a competitive edge which directly improves the company performance.…”
Section: Discussionsupporting
confidence: 93%
“…Ali & Mehreen, 2018). One of the major roles of HR is to make sure that employee with right skills and talent should stick with the organization for a greater length of time (Ifeoma, Purity, & Okoye-Nebo, 2015). Talent management is getting popularity as a tool for employees and organizational performance (Kimani & Waithaka, 2013).…”
Section: Talent Management and Organizational Effectivenessmentioning
confidence: 99%
“…Talent retention refers to the retention of skilled and talented individuals in the organization for a long period of time. One of the key roles of HR is to ensure that employees with right skills and talent sticks with the organization for a very long period of time (Ifeoma, Purity, & Okoye-Nebo, 2015). Attracting and hiring talented individuals is good for an organization but it is most important to retain these talents for as long as possible.…”
Section: Talent Retentionmentioning
confidence: 99%
“…This is due to the reduction in employee turnover, increase in employee motivation and commitment to the organization following the employee's satisfaction with the job and general stability that an organization enjoys when they are able to retain their talented employees. Ifeoma et al (2015) assert that retaining employees with the right skill and talent for a long period of time in an organization is the major role of the HR. This is as a result of the immense benefit to be derived from talented workforce.…”
Section: Talent Development and Organizational Effectivenessmentioning
confidence: 99%
“…The growing needs of the organizations to hire, attract, develop, and keep talented employees led to developing the concept of talent management until it became a strategic business challenge. (Ifeoma & Purity, 2015) It has also obtained significant research concern recently, to build a theoretical and practical framework to illustrate this new concept, and opinions differ about the definition of talent management (Meyers, 2019). But after reviewing the literature it was found that the idea of the concept of talent management is not new, it has appeared in the research conducted by Mckinsey studies "talent war" after which it was developed to be published as a book in 2001 (Latukha, 2015).…”
Section: Talent Managementmentioning
confidence: 99%